The persistently infected bovine viral diarrhea virus individual: prevalence, viral survival, and impact within commercial feeding systems - Stevens, Elliot Thomas (Kansas State University, 2009)
Bovine viral diarrhea virus (BVDV) has emerged as one of the most important infectious diseases in cattle. One particular important manifestation, after successfully establishing an in utero infection of the fetus during the first trimester, is the development of a persistently-infected BVDV (PI-BVDV) calf. Persistently infected BVDV animals are a continuous source of virus and can shed the virus in virtually all secretions and excretions, including nasal discharges, saliva, semen, urine, tears, milk, and, to a lesser extent, feces. The objectives of this research were to determine: 1) the effects of short term exposure (13 – 18 days on feed (DOF)) to PI-BVDV feeder cattle; 2) the outcome of testing and removing PI-BVDV feeder calves at time of feedlot arrival on health, performance, and carcass characteristics; 3) the survival of BVDV on materials associated with livestock production; and 4) characterization of testing and longitudinal prevalences for PI-BVDV beef cattle. Testing and removing PI-BVDV calves at 13 to 18 DOF was too late to remove a morbidity effect due to PI-BVDV exposure. However, mortality, performance, and carcass characteristics were not different in cattle exposed to PI-BVDV cattle. Additionally, there were no harmful outcomes when newly arrived feeder cattle were exposed to a PI-BVDV animal for one to two days following feedlot entry. A non-cytopathic, Type 1b, BVDV was capable of surviving after application to various materials used in livestock production. BVDV tended to survive longer on non-porous materials than porous materials. When in the presence of mucus, BVDV was protected from degradation for longer periods of time than when not in the presence of mucus. There was no difference in overall PI-BVDV prevalence within cattle sampled in 2006 and 2007. Cattle that weighed less than 300 lbs. had a greater likelihood of being PI-positive than cattle with increased weights. Several months of the year had a greater likelihood of having PI-positive animals. Based on operation, cow-calf and stocker operations had a greater likelihood of having PI-positive animals than did feedlot operations.
Keywords: Bovine; Bovine Viral Diarrhea Virus; Persistent Infection; Biology, Animal Physiology (0433); Biology, Microbiology (0410); Biology, Veterinary Science (0778)